New Case of Glyphosate Resistance in False-Star-Grass (Chloris distichophylla Lag.) Population, Southern Brazil - Vázquez-García, José G.; Golmohammadzadeh, Sajedeh; Palma-Bautista, Candelario; Rojano-Delgado, Antonia M.; Domínguez-Valenzuela, José A.; Cruz-Hipólito, Hugo E.; Plaza, Guido; Prado, Rafael De (Current Research Progress in Agricultural Sciences Vol. 8, 2025)
Chloris distichophylla Lag. commonly known as false-star-grass or weeping fingergrass, is found in areas where soybean and fruit crops are grown in southern Brazil. A population of false-star-grass, suspected of glyphosate resistance (GR), was collected from areas of soybean cultivation in Rio Grande do Sul, Brazil. The objective of this work was to characterize glyphosate-resistant C. distichophylla in southern Brazil. C. distichophylla seeds were collected from areas of soybean cultivation in Rio Grande do Sul, Brazil. A comparison was made with a susceptible population (GS) to evaluate the resistance level, mechanisms involved, and control alternatives. The dose-response assay showed differences in the GR50 and LD50 values of the GS and GR C. distichophylla populations. Glyphosate doses required to reduce the dry weight (GR50) or cause a mortality rate of 50% (LD50) were around 5.1–3 times greater in the GR population than in the GS population. The shikimic acid accumulation was around 6.2-fold greater in GS plants than in GR plants. No metabolized glyphosate was found in either GR or GS plants. Both populations did not differ in the enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) basal activity or in vitro inhibition of EPSPS activity by glyphosate (I50). The maximum glyphosate absorption was observed at 96 hours after treatment (HAT), which was twofold higher in the GS plants than in the GR plants. This confirms the first reported case of glyphosate resistance in C. distichophylla. In addition, at 96 HAT, the GS plants translocated more 14C-glyphosate than the GR ones. The best options for the chemical control of both C. distichophylla populations were clethodim, quizalofop, paraquat, glufosinate, tembotrione, diuron, and atrazine. The study confirmed the first case of glyphosate resistance in C. distichophylla. The first case of glyphosate resistance in C. distichophylla was due to impaired uptake and translocation. Chemical control using multiple herbicides with different modes of action (MOA) could be a tool used for integrated weed management (IWM) programs.